Composition, abundance and diversity of macro-benthic fauna and aquatic insects of Erelu reservoiur and its physical properties (2015)
Erelu Reservoir was studied between July 2012 and June 2013, to assess the composition, abundance and diversity of macro-benthic fauna, aquatic insects and its physical parameters. The water, benthic and aquatic insects were collected once every month from three stations. Highest mean value of transparency was 94.42± 5.49cm, Temperature 29.08 ± 0.38°C and Hydrogen ion concentration (PH) 7.27 ± O.l5mg/1. The range for transparency was (70-130)cm, (6.40-7.8) Mg/l for pH and (26-32°C) for temperature. Seven families of benthic macro-fauna; Ampullaridae, Viviparidae, Chironomidae, Lymneaidae, Planorbidae, Thiaridae and Margaritiferidae as well as eight families of aquatic insects; Gyrinidae, Notonectidae, Gerridae,Veliidae, Nepidae, Aeshnidae, Coenagrionidae and Libellulidae were recorded. A total number of 4,632 benthic individuals and 8,648 insects were recorded. Melanoides tuberculata dominated the benthic fauna with a total relative abundance of 90.71% while Planorbidae (Biomphalaria pfeifferi) were the least abundant (0.11 %) by number in the reservoir. Notonectidae (Notonecta sp.) dominated the aquatic insects with abundance of 92.43% while Nepidae (Lacotrephes japonensis) was the least abundant, (0.01 %). Margalef's index (H) in stations 1-3 was (0.60-1.14), Shannon Index (D)was (0.23-0.60), Evenness (E) was (0.41-0.90) for the benthic fauna while H= (0.35-0.50), D= (0.21-0.87) and E= (0.50-2.60) for the aquatic insects. The Margalef's index recorded across the stations for both benthic and aquatic insects showed that the reservoir was moderately polluted.